Sustainable recovery of rare Earth elements from industrial waste: A path to circular economy and environmental health - Pranav Prashant Dagwar; Syed Suffia Iqbal; Deblina Dutta (Waste Management Bulletin)
Rare earth elements (REEs) play a vital role in digitalization and industrialization. Naturally occurring in bastnasite, monazite, and xenotime, REEs are primarily concentrated in China, Australia, and the USA, leading to dependence on secondary sources. Recycling REEs from industrial waste such as E-waste, wastewater, red mud, slag, and fly ash offers a sustainable, low-emission, and energy-efficient solution. Advanced methods, including bio-metallurgy, have optimized recovery, achieving 80–95% efficiency for elements like Yttrium, Cerium, Neodymium, and Thorium. However, improper handling of secondary REE resources poses environmental and health risks. This study comprehensively explores REEs’ role in sustainable industrial growth, evaluating traditional and advanced recycling technologies. It also assesses the ecotoxicological impacts of REEs and emphasizes safety measures. Additionally, the review highlights circular economy strategies for sustainable development, addressing environmental challenges while promoting efficient resource utilization.